Notch-Hes1 Signaling Regulates IL-17A+γδ+T Cell Expression and IL-17A Secretion of Mouse Psoriasis-Like Skin Inflammation - Yanqin Wang; Xinxin Li; Xiaoyun Xing; Haibo Xue; Ruiqun Qi; Hong Ji; Lei Ma (Mediators of Inflammation)
Purpose. To evaluate the regulating effect of Notch-Hes1 signaling on IL-17A+γδ+T cell expression and IL-17A secretion in mouse psoriasis-like skin inflammation. Materials and Methods. Experimental mice were randomly divided into control group, model group (5% imiquimod- (IMQ-) treated mice), and intervention group (IMQ and γ-secretase inhibitor DAPT cotreated mice). The severity of psoriasis-like skin inflammation was evaluated by target lesion score based on the clinical psoriasis area and severity index (PASI). Flow cytometry detected IL-17A+γδ+T cell percentage. Quantitative real-time RT-PCR detected Hes1 mRNA expression. Enzyme-linked immunosorbent assay and western blot measured IL-17A serum concentration and protein expression. Additionally, splenic single cells from model mice were treated by DAPT to further evaluate the inhibitory effect of blocking Notch-Hes1 signaling on IL-17A+γδ+T cell differentiation and IL-17A secretion. Results. The spleen index, IL-17A+γδ+T cell percentage, Hes1 mRNA expression, IL-17A serum concentration, and protein expression were all significantly higher in model mice than control mice, while dramatically reduced in intervention mice by DAPT treatment, which also obviously alleviated the target lesion score, epidermal hyperplasia, and dermal inflammatory cell infiltration of intervention mice. In vitro study demonstrated that DAPT treatment could result in dose-dependent decrease of IL-17A+γδ+T cell percentage and IL-17A secretion in splenic single cells of model mice.